2020
DOI: 10.1155/2020/1247946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saffron Extract and Crocin in Serum Metabolites of Induced Obesity Rats

Abstract: The effect of saffron extract (Crocus sativus L.) and its primary compound crocin was studied on an induced obesity rat model. Our study is aimed at investigating and comparing the metabolite changes in obese and obese treated with saffron extract and crocin and at improving the understanding of the therapeutic effect of saffron extract and crocin. Two different doses of saffron extracts and crocin (40 and 80 mg/kg) were incorporated in a high-fat diet (HFD) and were given for eight weeks to the obese rats. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Saffron treatment returned the mice to their normal behavior after 24 hours indicating its efficacy in restoring behavioral deficits associated with our injury model. Tracking weight changes in mice throughout the study showed that the injury affects mice weight and because saffron has proved to be a satiety enhancer [61], reduces blood biomarkers associated with obesity [62], and exert anti-obesity and body weight management effects in rats fed with high-fat diet [63]. Thus, we can assume that mice were able to gain weight due to the neuroprotective effect of saffron in restoring motor deficits which facilitated their access to food.…”
Section: Plos Onementioning
confidence: 98%
“…Saffron treatment returned the mice to their normal behavior after 24 hours indicating its efficacy in restoring behavioral deficits associated with our injury model. Tracking weight changes in mice throughout the study showed that the injury affects mice weight and because saffron has proved to be a satiety enhancer [61], reduces blood biomarkers associated with obesity [62], and exert anti-obesity and body weight management effects in rats fed with high-fat diet [63]. Thus, we can assume that mice were able to gain weight due to the neuroprotective effect of saffron in restoring motor deficits which facilitated their access to food.…”
Section: Plos Onementioning
confidence: 98%
“…Crocus sativus L., known as saffron, is used in folk medicine for various therapeutic purpose [15]. Saffron is widely cultivated in Middle East and Mediterranean countries [16,17]. Crocin is one of the major biologically active ingredients of saffron [18].…”
Section: Introductionmentioning
confidence: 99%